Resumption of studies on pollen deposition in the III Campus of the Jagiellonian University in Krakow - Bokalska-Rajba, Joanna; Nalepka, Dorota (Ecological Questions, 2017)
Abstract. Collected in 2016 samples from the surface and from the soil profiles, contained enough amounts of sporomorphs to have started studies on pollen deposition near the III Campus of the Jagiellonian University in Krakow. Preliminary results of the first year of research are presented (percentage pollen diagram and pollen accumulation rate) and compared with chosen results from previous years of research.